Studiare la polarizzazione politica nello “shockdown mediale” - Iannelli, Laura; Splendore, Sergio; Valeriani, Augusto; Marino, Giada (Mediascapes journal, 2020)
In this paper, we discuss implications that the lockdown experience had on goals, methodological approaches, and topics of interest of a longitudinal study that we are conducting on political opinion polarization among Italian citizens in the hybrid media system. We also present some of the data collected in the first wave of our survey, fielded in May 2020, after two months of media shock. We provide a preliminary snapshot of the "state" of polarization concerning some controversial issues about the protection of public health. Additionally, we discuss some relations between citizens’ "older" and "newer" media experiences during the lockdown and the likelihood of assuming extreme positions on these topics. Lastly, we address some analytical choices to be taken in the next stages of our study (“phase 2”).